Hollywood on the Hudson : film and television in New York from Griffith to Sarnoff - Koszarski, Richard (Rutgers University Press, 2008)
Thomas Edison invented his motion picture system in New Jersey in the 1890s, and within a few years most American filmmakers could be found within a mile or two of the Hudson River. They planted themselves here because they needed the artistic and entrepreneurial energy that D.W. Griffith realized New York had in abundance. But as the going rate for land and labor skyrocketed and their business grew more industrialized, most of them moved out. The way most historians explain it, the role of New York in the development of American film ends here. In Hollywood on the Hudson, Richard Koszarski r.